A Study of Speech Styles Used by the Host in Mata Najwa and Catatan Najwa - Angelia Anggraini (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
I conducted this study to investigate speech styles used by Najwa as the host in Mata Najwa Part 8 - Republik Digital: Bisnis Digital dan Peluangnya, Mata Najwa Part 9 - Republik Digital: Tips Membangun Bisnis Digital, and Catatan Najwa Part 2 - Ide-Ide Brilian Bos Sido Muncul to the younger and older guests. The underlying theory used is Speech Style from Chaer and Agustina (2010) and Indonesian: Standard Indonesian (Bahasa Baku) and Non-standard Indonesian (Bahasa Tidak Baku) from Prihantini (2015). This study was done using a qualitative approach. The data analysis revealed that Najwa as the host of Mata Najwa and Catatan Najwa, used formal style, consultative style, casual style, and intimate style when talking to her younger and older guests. Najwa did not use the frozen style when talking to her guests. Keywords: speech styles, age, host, talk show